Пользовательского поиска

wy1' = wx1'×tg(b)+wy2'/cos(b) (4')

wz1' = wx0'×sin(a) + wz0'×cos(a)

 

wx2 = wx1×cos(b) + wy1×sin(b) (5)

wx2' = wx1'×cos(b) + wy1'×sin(b) (5')

 

(2), (3) (1), :

 

Jy1×wy1' + (Jx1-Jz1)×wx1×wz1 + Jzx1×wx12 - Jxz1×wz12 +

+ Jzy1×wx1×wy1 - Jxy1×wy1×wz1 - Jyx1×wx1' - Jyz1×wz1' = My1 (6.1)

 

Jx2×wx2' + (Jz2-Jy2)×wy2×wz2 - 2×Jzy×wy22 + Jyz2×wz22 +

+ Jyx2×wx2×wz2 - Jzx2×wx2×wy2 - Jxz2×wz2' - Jxy2×wy2' = Mx2 (6.2)

 

Jy2×wy2' + (Jx2-Jz2)×wx2×wz2 + Jzx2×wx22 - Jxz2×wz22 +

+ Jzy2×wx2×wy2 - Jxy2×wy2×wz2 - Jyx2×wx2' - Jyz2×wz2' = My2 (6.3)

 

Jz2×wz2' + (Jy2-Jx2)×wx2×wy2 + Jxy2×wy22 - Jyx2×wx22 +

+ Jxz2×wy2×wz2 - Jyz2×wx2×wz2 - Jzx2×wx2' - Jzy2×wy2' = Mz2 (6.4)

 

(6.2), (6.3), (6.4) , (6.1) Y1. (6.1), (6.2), (6.3) A, B C, , :

 

My1 = A + B × sin(b) + C × cos(b) (7)

 

(7) A, B C y1.

 

y1=Jxz1{wx12-wz12}+

+Jxz2cos(b)wx22-Jyz2sin(b)wy22+

+{Jyz2sin(b)-Jxz2cos(b)}wz22+

+{Jyz2cos(b)-Jxz2sin(b)}wx2wy2+

+{Jxy2sin(b)+(Jx2-Jz2)cos(b)}wx2wz2+

+{(Jz2-Jy2)sin(b)-Jxy2cos(b)}wz2wy2+ (8)

+{Jx2sin(b)-Jxy2cos(b)}wx2' +

+{Jy2cos(b)-Jxy2sin(b)}wy2'-

-{Jxz2sin(b)+Jyz2cos(b)}wz2'+

 

 Rambler's Top100